Digital Discontents: Freedoms and constraints in platform social work - Lauri Goldkind; Barbara Pohl; Lea Wolf (Social Work and Society, 2023)
Across the diverse domains of social work in the United States, new digital tools are altering the worker experience. This paper offers the example of one case in which technology has been transforming social work practice, documenting how clinical social workers who contract with for-profit tele-mental health platforms describe their experience of providing therapy to clients. Privately owned, technology driven, direct to consumer tele-mental health platforms have become a new actor in the fragmented American mental health landscape. This qualitative study presents findings from a sample of 22 professional social workers to observe how this novel context changes the experience of providing therapy. Participants described being drawn to contract with platforms by promised freedoms: flexible hours and remote work, and the opportunity to develop skills or to cultivate their own private practices. Simultaneously, they observed how working on platforms constrains the provision of therapy that they offer to their clients. In particular, participants shared that they were required to cultivate new skills of creating digital intimacy within new two dimensional and asynchronous spaces. They also noted that they engaged in invisible and unpaid forms of labor in order to maintain clients and to provide services that aligned with their professional values. As technological tools and systems continue to shape the future of social work practice, professionals will need to be alert to how these forces shape their own professional potentials and to the ethical implications of a changing service landscape. Descriptive outcomes of this study offer intersect with research literature on ghost work, platform labor, and the commercialization of care.